Factors Affecting the Interest of Accounting Students in West Sumatra in Becoming Sharia Auditors - Elvia, Mairisa; Putriana, Vima Tista (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to examine the influence of Islamic accounting knowledge, social environment, and labor market considerations on the interest of accounting students in West Sumatra to become Islamic auditors. The sampling technique used was convenience sampling, with 427 respondents obtained. The results of the study indicate that Islamic accounting knowledge and social environment do not have a significant influence on the interest of accounting students to become Islamic auditors. Meanwhile, labor market considerations and religious considerations have a positive influence on accounting students' interest in becoming Sharia auditors. The practical implications of this study include the need for universities, professional associations, and related institutions to provide learning opportunities for students regarding Sharia auditing, in order to improve the competence of future Sharia auditors.